2021
DOI: 10.1149/1945-7111/ac3200
|View full text |Cite
|
Sign up to set email alerts
|

The Superior Electrical Conductivity and Anodic Stability of Vanadium-Doped Ti4O7

Abstract: The effectiveness of Magnéli phase titanium oxides (Ti n O 2n−1 , 4 ⩽ n ⩽ 10), promising alternatives to carbon-based materials in aqueous electrochemical technologies, is limited by their instability at strongly oxidizing electrode potentials. Ti 4 O 7 and Ti 5 O 9 , the most electrically-conductive Ti n O 2n−1 , passivate in the harsh conditions demanded by fuel cells, batteries, and devices for the electrochemical treatment of water. Among other properties relevant to electrodes, doping of Ti n O 2n−1 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…38 The superiority of the electrical conductivity of (Ti 1-x V x ) 4 O 7 for x > 0 is attributed to the presence of vanadium, whose increasing concentration in Ti 4 O 7 is observed to reduce its electrical resistivity. 58 Compared with our previous report, 38 a further improvement in the electrical conductivity of the materials used currently is attributed to a longer time and higher temperature of sintering, which is expected to improve fusion between grains and therefore decrease the electrical resistance between particles. Values of electrical conductivity are still less than those observed for singlecrystal measurements of Ti 4 O 7 : 1,000-2,000 S cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The superiority of the electrical conductivity of (Ti 1-x V x ) 4 O 7 for x > 0 is attributed to the presence of vanadium, whose increasing concentration in Ti 4 O 7 is observed to reduce its electrical resistivity. 58 Compared with our previous report, 38 a further improvement in the electrical conductivity of the materials used currently is attributed to a longer time and higher temperature of sintering, which is expected to improve fusion between grains and therefore decrease the electrical resistance between particles. Values of electrical conductivity are still less than those observed for singlecrystal measurements of Ti 4 O 7 : 1,000-2,000 S cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Over a range of 0.1-10 mA cm −2 , the cell voltage in supporting electrolyte increases from that near the equilibrium cell potential for the electrolysis of water, 1.23 V, to that approaching 5 V. As discussed earlier, Ti 4 O 7 as well as (Ti 0.98 V 0.02 ) 4 O 7 are poor electrocatalysts for the water splitting reactions including the OER. 38,61 Additionally, the cathode compartment is composed of a carbon-based GDL, which exhibited modest catalytic behavior toward the complementary water splitting reaction (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some studies on the electrochemical properties of doped Ti 4 O 7 . According to English et al, 31 V and Fe as dopants can improve the electronic conductivity of Ti 4 O 7 due to the increased carrier concentration, and the V-doped Ti 4 O 7 anode exhibited greater stability in the oxygen evolution process (H 2 O → O 2 + H + + e − ). Xu et al 32 prepared La-doped Ti 4 O 7 electrodes and found that the doped electrodes provided a higher number of surface oxygen vacancies, resulting in increased •OH generation efficiency (Reaction 3).…”
Section: Introductionmentioning
confidence: 99%
“…There have been some studies on the electrochemical properties of doped Ti 4 O 7 . According to English et al., 31 V and Fe as dopants can improve the electronic conductivity of Ti 4 O 7 due to the increased carrier concentration, and the V‐doped Ti 4 O 7 anode exhibited greater stability in the oxygen evolution process (H 2 O → O 2 + H + + e − ). Xu et al 32 .…”
Section: Introductionmentioning
confidence: 99%